Pelajaran Pendidikan Agama Islam Yang Di Minati Siswa-Siswi Madrasah Tsanawiyyah Sederajat - Annisa Oktafera (Lentera Jurnal, 2025)
Interest is a desire that motivates students to participate in learning. Interest is very influential on the goals of students in the future. With interest, students will build various desires to achieve these desires in the future. At the same time, Islamic religious education learning is learning that learns about everyday life by referring to the Koran and hadith. The Islamic Religious Education learning is developing in Madrasah Ibtidaiyyah, Madrasah Tsanawiyyah, and Madrasah Aliyah. There are even many schools that prioritise Islamic religious education learning compared to general knowledge, from several schools surveyed, where Islamic religious education learning teachers use the lecture method. Some teachers have used the audio-visual method. This study aims to determine the interest of Madrasah Tsanawiyyah students in Islamic Religious Education learning, especially in the current era.